On the correlation between aerodynamic drag and wake flow for a generic high-speed train. Issue 215 (August 2021) - Li, Xiao-Bai; Liang, Xi-Feng; Wang, Zhe; Xiong, Xiao-Hui; Chen, Guang; Yu, Yi-Zheng; Chen, Chun-Mian
Abstract: The current research attempts to describe the association between the aerodynamic drag and flow structures induced by train running in time-averaged and time-dependant views. A ICE2 train model is used as the research object, with the flow field solved by Large Eddy Simulation (LES). The validation is carried out through comparison with existing research data, and grid independence study in terms of time-averaged and second-order statistics. Numerical results are firstly presented by description of the time-averaged near wake flow topology based on surface flow visualization. Then, the wake integration method is used both time-averaged and instantaneously to link the aerodynamic force with integrated flow quantities on different wake planes: from the time-averaged perspective, the contribution of different flow terms to total drag is presented and compared; from the instantaneous perspective, the overall wake variation tendency is linked to the fluctuating component of aerodynamic force, based on the wake convection velocity and downstream distance of wake planes. The dynamic features of flow quantities in different locations are presented, with cross-correlation method used to describe the correlation between fluctuating aerodynamic drag and wake motion. Approaches and findings presented in the current study could serve as fundamentals which support future study. Highlights: Large eddy simulation employed to solve flow field around a generic ICE2 high-speed train model. Surface flow visualization techniques utilized to illustrate the time-averaged near wake flow topology. Wake integration method applied to link the aerodynamic force with integrated flow quantities on different wake planes. Dynamic features of flow quantities presented, with cross-correlation method used to describe correlation between aerodynamic drag and wake motion.